DEVELOPMENT OF A METHOD FOR LABORATORY DIAGNOSTICS OF ACUTE HYPOTENSIVE DRUGS POISONING - E. S. Melnikov; M. V. Belova (Сеченовский вестник, 2022)
The method of express detection of hypotensive drugs (atenolol, propranolol, nifedipine, enalaprile and verapamil) in urine samples of patients with acute poisonings was developed. The optimum conditions of group identification of hypotensive drugs using TLC were found. Analysis by GC-MS allows to detect both the native substances and their metabolites. The developed method of analysis of antihypertensive drugs can be used for the diagnosis of acute poisoning.